INTRODUCTIONOF PROJECT METHOD IN ENGLISH LESSONS - Дементьева, А.В. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2024)
This article discusses the experience of introducing the practical project method into English lessons. The article provides justification for the use of this method and its advantages for students. The work also describes the stages of preparation for the project.
Keywords: English language; school; motivation; project method